Building a testable shear viscosity across the QCD phase diagram - Mclaughlin, Emma; Rose, Jacob; Dore, Travis; Parotto, Paolo; Ratti, Claudia; Noronha-Hostler, Jacquelyn (Physical Review C - Nuclear Physics, 2022)
Current experiments at the Relativistic Heavy Ion Collider (RHIC) are probing finite baryon densities where the shear viscosity to enthalpy ratio ilT /w of the quark gluon plasma remains unknown. We use the hadron resonance gas (HRG) model with the most up-to-date hadron list to calculate ilT /w at low temperatures and at finite baryon densities pB. We then match ilT /w to a quantum-chromodynamics-based shear viscosity calculation within the deconfined phase to create a table across T, mu B for different crossover and critical point scenarios at a specified location. We find that these new ilT /w(T, mu B) values would require initial conditions at significantly larger pB, compared to ideal hydrodynamic trajectories, to reach the same freeze-out point.
CRIS-Team WoS Importer:2022-03-04